Distribusi Dan Transportasi Bio Solar Di Jawa Timur - Kushariyadi (Universitas Nusa Putra, 2023)
Government Regulation Number 36 of 2004 concerning Downstream Oil and Gas Business Activities, the government regulates, fosters, and supervises the implementation of downstream business activities which includes guaranteeing the availability and smooth distribution of fuel throughout the territory of the Unitary State of the Republic of Indonesia. Vehicle Routing Problem (VRP) which is a form of route problem involving vehicles to distribute goods to customers with the aim of minimizing the total distance, minimizing the use of vehicles and the overall distribution time which is expected to reduce errors in selecting gas stations into road routes. Based on the application of the fuel distribution system to gas stations in East Java, especially in the Bojonegoro Regency area using the Vehicle Routing Problem (VRP) method, using a tanker with a capacity of 40 KL is more effective than a tanker with other capacities, distance and operating costs for a tanker of 40 KL the results after the application of the VRP method are more effective than the current distribution patterns, if the VRP method is used it will produce several benefits, including reducing the total mileage of the previous tank car from 3,740 KM to 1,058 KM compared to the current average total mileage of TBBM Semarang-To gas stations in Blora. There was a saving in the cost of diesel fuel from IDR 25,432,000 to IDR. 7,194,400 per day considering there is great efficiency, the pattern for sending Bio Solar fuel from TBBM Tuban to gas stations in Bojonegoro Regency uses a new route using a tanker capacity of 40 tons.